Determinants Exports of Plastic Industry Products and Their Implications for Trade Balance and Employment Case Studies of Several Asean Countries - Prabowo Subianto; Dian Damayanti; Toni Toharudin; Darwati Susilastuti; Juni Gultom; Cicih Ratnasih; Bambang Bernanthos; Esti Royani (Communications of International Proceedings, 2025)
This research uses multiple linear regression analysis exchange rate, Foreign Direct Investment, inflation, quantity of plastic export production, and logistics infrastructure on plastic industry product exports in several ASEAN countries Data analysis proves that the variables of currency exchange rate, Foreign Direct Investment, inflation, quantity of plastic export production, logistics infrastructure on plastic industry product exports in ASEAN countries all affect exports in Southeast Asian countries. Stating that currency exchange rate, FDI, inflation, quality and quantity of plastic export production, and logistics infrastructure simultaneously affect plastic industry product exports to several ASEAN countries. To test this hypothesis, multiple regression analysis can be used with plastic industry product exports as the dependent variable, while the rupiah exchange rate, FDI, inflation, quality and quantity of plastic export production, and logistics infrastructure as independent variables. Currency exchange rate Hypothesis: If the currency weakens, exports increase because the product price is more competitive. Possible results: Negative or positive coefficient, depending on the sensitivity of plastic prices to exchange rates. FDI (X2): Hypothesis: FDI increases plastic production capacity and exports. Possible outcomes: Positive coefficient, indicating that the greater the FDI, the higher the plastic industry exports. Inflation (X3): Hypothesis: High inflation increases production costs and suppresses the competitiveness of plastic exports. Possible outcomes: Negative coefficient, indicating that high inflation tends to decrease exports. Plastic export production quantity (X4): Hypothesis: Increasing the quality and quantity of production increases exports. Possible outcomes: Positive coefficient, indicating that better production increases exports. Logistics infrastructure (X5): Hypothesis: Better infrastructure reduces logistics costs and increases exports. Possible outcomes: Positive coefficient, indicating that the better the infrastructure, the higher the exports. The interaction between these variables is often synergistic. In exports for example, investment in the plastic industry attracts FDI in the plastic industry sector but also increases economic growth in Indonesia and Southeast Asian countries which can reduce the adverse effects of the global economic crisis. Similarly, the vast market potential and environmentally friendly and sustainable plastic industry policies can work together to create an attractive environment for investors and plastic industry exports.
Keywords: Law; exchange rate; Foreign Direct Investment; inflation; quantity; export; logistics infrastructure; Trade of balance and employment; ASEAN